Seronegative hepatitis C virus infection in patients with lymphoproliferative disorders. Issue 6 (20th October 2013) - Kisiel, E.; Radkowski, M.; Pawelczyk, A.; Horban, A.; Stanczak, J.; Bukowska‐Ośko, I.; Caraballo Cortes, K.; Kaźmierczak, J.; Popiel, M.; Laskus, T.
Summary It has been reported that hepatitis C virus (HCV) RNA may be present in serum and/or lymphoid cells in the absence of specific circulating antibodies. The current study analysed seronegative HCV infection in patients with lymphoproliferative disorders. We studied 77 anti‐HCV‐negative patients (45 male and 32 female, mean age 54.8 ± 14.2 years) with various lymphoproliferative disorders. HCV‐RNA was detected by RT‐PCR in plasma, peripheral blood mononuclear cells (PBMC) and bone marrow. Furthermore, the presence of viral nonstructural protein 3 (NS3) was determined in PBMC and bone marrow by immunostaining. HCV‐RNA was detectable in at least one compartment in 27 (35.1%) patients. Viral RNA was found in bone marrow in 22 patients (28.6%), in PBMC in 13 (16.9%) and in plasma in 10 (13%) patients. In nine patients, evidence of infection was confined to the bone marrow compartment. Viral load in HCV‐RNA‐positive plasma ranged from 15 to 1.17 × 103 IU/mL. NS3 was detected in all but two HCV‐RNA‐positive bone marrow samples and in all but one HCV‐RNA‐positive PBMC samples. All 27 HCV‐RNA‐positive patients remained anti‐HCV‐negative when tested again after 6–12 months, but only four remained HCV‐RNA positive. In conclusion, among patients with lymphoproliferative disorders, HCV can be present in plasma, PBMC and bone marrow despite the lack of circulating specific antibodies. Further studies are required to analyse the phenomenon of seronegative infection and to determine whether such patients are infectious.